Compound-based Chinese medicine formula: From discovery to compatibility mechanism. (23rd May 2020) - Luan, Xin; Zhang, Li-Jun; Li, Xiao-Qin; Rahman, Khalid; Zhang, Hong; Chen, Hong-Zhuan; Zhang, Wei-Dong
Abstract: Ethnopharmacological relevance: Chinese medicine formula (CMF) has a long history of clinical use in the treatment of various diseases under the guidance of traditional Chinese medicine (TCM) theory. The application of CMF can be divided into three levels, crude extracts, homologous compounds mixture, and specific compounds. However, the modern scientific connotation of the CMF theory has not been clarified. Aim of the review: To critically evaluate the research strategy for the investigation of compound-based CMF (CCMF). Materials and methods: The related information was collected from the scientific databases, including CNKI, Elsevier, ScienceDirect, PubMed, SpringerLink, Web of Science, and Wiley Online. Results: The research design including discovery, screening, optimization, pharmacodynamics models, and target research techniques including the targets for compatibility compounds were evaluated. Essentially it has been evaluated that the in vitro multicellular three-dimensional culture or organoid model has been proposed for the optimization model for compatibility research of CCMF. Based on these, the traditional compatibility theory of CMF, such as Monarch-Minister-Assistant-Guide (Jun-Chen-Zuo-Shi in Chinese), can probably be elucidated by the CCMF research. Conclusions: CCMF has the clear advantage of providing the exact composition and controllable quality of modern medicines, in addition to having the characteristics of multi-ingredients and multi-targets synergistic effects of TCM. However, CCMF is still associated with challenges which need to be addressed for its future use. Graphical abstract: Image 1